1998
DOI: 10.1200/jco.1998.16.9.3016
|View full text |Cite
|
Sign up to set email alerts
|

High risk of leukemia after short-term dose-intensive chemotherapy in young patients with solid tumors.

Abstract: Repetitive high-dose use of alkylating agents given with topoisomerase-II inhibitors is strongly leukemogenic, even with modest cumulative doses of each drug. This finding is notable for the following reasons: (1) it undermines predictions that limited use of high-dose chemotherapy might be minimally leukemogenic, and (2) it contrasts strikingly with the previously reported low risk of t-AML following treatment of pediatric solid tumors with chemotherapy lacking the alkylator dose-intensity and prominence of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 0 publications
1
49
1
1
Order By: Relevance
“…51,52 Furthermore, the use of DNA-damaging agents, such as radiotherapy and alkylating agents, have been clearly established as independent risk factors for secondary tumors in pediatric patients. 53,54 Although no data on telomere function was provided in these studies, the cytogenetic abnormalities observed might have been caused or aggravated by short or unstable telomeres. In this regard, it has been reported that cisplatin, a nonclassical alkylating agent often used for the treatment of childhood solid tumors, directly targets telomeric DNA.…”
Section: Leukemiamentioning
confidence: 99%
“…51,52 Furthermore, the use of DNA-damaging agents, such as radiotherapy and alkylating agents, have been clearly established as independent risk factors for secondary tumors in pediatric patients. 53,54 Although no data on telomere function was provided in these studies, the cytogenetic abnormalities observed might have been caused or aggravated by short or unstable telomeres. In this regard, it has been reported that cisplatin, a nonclassical alkylating agent often used for the treatment of childhood solid tumors, directly targets telomeric DNA.…”
Section: Leukemiamentioning
confidence: 99%
“…Six months after starting therapy, peripheral monocytosis and cytopenias appeared. The G-banded marrow karyotype obtained 12 months from diagnosis as a routine test was 46,XY,del(11)(q23) [8]͞46,XY [12] (3,8). Seventeen months after starting therapy, the marrow was replaced by FrenchAmerican-British M4 leukemic blasts.…”
Section: Case Reportmentioning
confidence: 99%
“…1). The incidence of leukemia is as high as 20% with intensive alkylating agent regimens for pediatric solid tumors (2,3). The incidence of epipodophyllotoxin-related cases is 2-3% (4).…”
mentioning
confidence: 99%
“…6,7 Childhood cancer survivors can also develop AML or MDS after treatment with growth factors (GFs), in combination with etoposide, anthracyclines, and radiotherapy. However, it is difficult to distinguish the contribution of GF versus intensified therapy and the effect of intensity 8 or cumulative doses of chemotherapy 9,10 in the development of secondary hematological malignancies.…”
mentioning
confidence: 99%